"Pale, male, and stale"? An analysis of introductory readers in political science. (22nd December 2021) - Scola, Becki; Bucci, Laura C.; Baglione, Lisa
Abstract: Scholarship indicates that women and gender are underrepresented in Political Science textbooks, particularly those in American Politics. We complement those analyses by focusing on the "companion readers" often paired with textbooks. Readers give students a glimpse at "real political science, " showing how the field is studied and what political scientists value. Do the readers convey that "women also know stuff, " women are political actors, and gender is a relevant construct? The answer to each of these three questions is a resounding no. Analyzing women and gender representation in readers for three introductory sub-fields (American, Comparative, and Global Politics), we find a strong preference toward scholarship by men. Our results indicate only a small proportion of women authors and an even lower percentage of articles that focus on women. Moreover, the readers have not changed over time resulting in readers that are still "pale, male, and stale." Because readers offer a snapshot of the field, and may be adopted passively in an introductory course, we argue that the absence of women harms students and political science itself.